The Border Development in Biski Beach Tourism in Riau Province - Afrizal Afrizal; Mimin Sundari Nasution; Mayarni Mayarni (Universitas Sultan Ageng Tirtayasa, 2022)
Pasir Limau Kapas Subdistrict is located in Rokan Hilir Regency, which has interesting tourist destinations but needs to be developed. In particular, Biski Beach tourism, which is visited by many local people and those from outside the area, but in reality, it is still far from what is expected, even though the potential for natural tourism objects is very feasible. A solution is sought. This is an interesting issue to be discussed. Pasir Limau Kapas Subdistrict [Palika], Rokan Hilir Regency, Riau Province, is an underdeveloped, isolated, and outermost area. This position makes welfare an important and major issue. Important and main issues related to welfare include minimal and slow infrastructure development and ambiguous development policies [the average policy issued overlaps and does not support each other related to development in border areas]. Based on various important issues, this study aims first to explain how the development of the border area (Case Study: Biski Beach Tourism Object, Pasir Limau Kapas District, Rokan Hilir Regency). The research approach used is qualitative with a descriptive analysis method. Primary and secondary data were gathered through document reviews, interviews with informants chosen using the purposive sampling technique, and observations and literature reviews.After collecting the data, it was analyzed by means of the Interactive Analysis Model. The theory used in this research is the Theory of Regional Development according to Riyadi (2000). There are three indicators of the success of regional development that can be seen. The first is productivity, the second is efficiency, and the last is community participation, which can ensure the continuity of the implementation of a program in an area. Based on these indicators, it is known that the development of the border area is not optimal.